Identidade profissional e de gênero no contemporâneo - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present research understands, through studies of language, sexuality and dis-course, how the relationship of sexual orientation with the exercise of the profession by self-declared gay journalists occurs. This is a monographic study that has a quali-tative approach and is supported by a theoretical foundation on the construction of the subject for discourse theories, for Queer Theory and Journalism. Using the semi-struc-tured interview method and life stories, the testimonies of ten (10) self-declared gay journalists were reflected on, divided into two groups: those in the profession and those by academic training. It was identified that professionals seek difficulties in the social imaginary about this relationship, even before working in the labor market, which re-sults in self-censorship in the daily lives of journalists to avoid sanctions by the institu-tion, proven by the Organizational Theory of journalism.
Keywords: Jornalismo; Homossexualidade; Profissões; Teoria Queer; Journalism; Homosexuality; CNPQ::CIENCIAS SOCIAIS APLICADAS